1989
DOI: 10.1073/pnas.86.24.9803
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the gene encoding the yeast protein BTF1Y, which can substitute for the human TATA box-binding factor.

Abstract: An activity (designated BTF1Y) in extracts of Saccharomyces cerevisiae can substitute for the human TATA box-binding factor BTF1 in a reconstituted transcription system containing the adenovirus 2 major late promoter, RNA polymerase B (II), and the basic transcription factors BTF2, BTF3, and STF. We have purified BTF1Y to homogeneity, using as assays reconstitution of in vitro transcription and DNase I footprinting on the TATA element. Both activities copurified with a 27-kDa polypeptide as determined by SDS/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 32 publications
3
74
0
Order By: Relevance
“…We found that the C-terminus of TBP was essential for TBP-TBP interaction. The C-terminal domain of TBP has multiple motifs/domains for DNA binding (basic repeat, direct repeat and sigma homology) (38)(39)(40). X-ray crystallography has shown that TBP forms a saddle shape structure (23).…”
Section: Multinerization Of Tbp In Solutionmentioning
confidence: 99%
“…We found that the C-terminus of TBP was essential for TBP-TBP interaction. The C-terminal domain of TBP has multiple motifs/domains for DNA binding (basic repeat, direct repeat and sigma homology) (38)(39)(40). X-ray crystallography has shown that TBP forms a saddle shape structure (23).…”
Section: Multinerization Of Tbp In Solutionmentioning
confidence: 99%
“…13 We have previously identified BTF3 as a differentially expressed gene in PDAC and chronic pancreatitis (CP). 14,15 In the present study we: (1) analyzed the expression of BTF3 mRNA and protein in the normal and diseased pancreas (CP and PDAC) and pancreatic cancer cell lines, and the localization of BTF3 in these tissues; (2) analyzed the functional consequences of BTF3 silencing in pancreatic cancer cell lines in terms of resistance to chemo/radiotherapy-induced apoptosis, and (3) used a DNA micro-array analysis to identify regulation of genes after BTF3 silencing, in order to specify the role of BTF3 in the transcriptional regulation of tumor-associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…Basic transcription factor 3 (BTF3), also known as nascent polypeptide-associated complex b (NACB), is a 27 KD protein 1,2 that is involved in the initiation of transcription by RNA polymerase from proximal promoter elements such as the TATA box and CAAT box sequences. 1,3,4 BTF3 is present in two isoforms: BTF3a, which has the transcription characteristics of BTF3, and BTF3b, which lacks the first 44 amino acids of BTF3a and is transcriptionally inactive.…”
Section: Introductionmentioning
confidence: 99%
“…There are no significant homologs of either subunit of VETF in a library of translated GenBank version 63.0 sequences, which includes the amino acid sequences of a number ofbacterial a factors. In addition, no significant homology was found between VETF and the sequenced eukaryotic general transcription initiation factors, human RAP30 (40) and yeast TFIID (41)(42)(43)(44).…”
mentioning
confidence: 99%